Isn't it romantic [videorecording (DVD)] - Strauss-Schulson, Todd, 1980-; Wilson, Rebel; Wilson, Rebel; DeVine, Adam, 1983-; Hemsworth, Liam, 1990- (Warner Bros. Entertainment, 2019)
A young woman struggling to find true love finds herself trapped inside of a romantic comedy film.